2019
DOI: 10.1111/ane.13075
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring of gabapentin in various indications

Abstract: Objectives Gabapentin has been increasingly used in various indications in recent years. Despite variable pharmacokinetics, therapeutic drug monitoring (TDM) is scarcely described in other indications than epilepsy. The aim of the study was to investigate the use and pharmacokinetic variability of gabapentin in epilepsy and non‐epilepsy indications and to further evaluate the use of TDM in patients with restless legs syndrome (RLS). Materials & Methods Population‐based data from the Norwegian Prescription Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In recent years several new ASMs have been introduced to the market, and around 30 different drugs are available internationally 1–3 . The armamentarium of drugs to choose from helps to tailor the treatment for groups and individuals with epilepsy and also in other disorders, that is, psychiatry and pain management 3–7 . Pharmacological challenges with all these drugs are numerous and therefore warrant detailed knowledge of the pharmacodynamic and pharmacokinetic properties of the drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years several new ASMs have been introduced to the market, and around 30 different drugs are available internationally 1–3 . The armamentarium of drugs to choose from helps to tailor the treatment for groups and individuals with epilepsy and also in other disorders, that is, psychiatry and pain management 3–7 . Pharmacological challenges with all these drugs are numerous and therefore warrant detailed knowledge of the pharmacodynamic and pharmacokinetic properties of the drugs.…”
Section: Introductionmentioning
confidence: 99%
“…GBP is recommended against partial epilepsy with/without secondary generalization and can be used in patients over three years of age. In addition, it may be used for neuropathic pain, restless legs syndrome, fibromyalgia, trigeminal neuralgia, multiple sclerosis, headache, anxiety, and post-operative pain [ 39 ]. In general, GBP is well tolerated and its few adverse effects include somnolence (in 19% of patients), dizziness (17%), ataxia (13%), fatigue (11%), nystagmus (8%) and headache (8%).…”
Section: Newer Antiepileptic Drugsmentioning
confidence: 99%
“…9 Hence, TDM must be used to find whether the patient's poor response to increasing drug dose causes disorder in absorption or not. 17 The importance of nanocomposites and nanoparticles in the manufacture of electrochemical sensors is very important, especially in the fields of medicine, pharmacy, and energy. For example, a study demonstrated that EGT biosensors could be extended with changing enzymes or nanomaterials, or hybrid nanomaterials for specific analyte detection.…”
mentioning
confidence: 99%